Arts and Design Discourse in Idealogy Journal: Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Taharuddin, Nurul Shima; Rosman, Muhammad Redza; Nazrin, Nizar; Md Nazri, Haslinda (Idealogy Journal, 2022)
Arts and Design Discourse